(untitled) (Journal of Engineering, 2005)
Shell foundations are generally found to be economic under conditions of heavy loads and weak soils as small amount of reinforcement is needed due to occurrence of compressive stresses in most parts of the foundation. Depending upon their size, conical shells can serve as footings for columns while inverted domes shells can serve as rafts for tanks supported on a circular row of columns. This paper describes 3-D finite element models, the eight nodes degenerated shell and the twenty nodes brick elements which are used herein. The models which may be adopted in the material nonlinear analysis of reinforced concrete shell foundations are described briefly in this paper. The present study results give good agreement compared with available experimental values about 5% in displacements.